Liver Biopsy Can Be Safely Performed in Pediatric Acute Liver Failure to Aid in Diagnosis and Management. Issue 4 (October 2018) - Chapin, Catherine A.; Mohammad, Saeed; Bass, Lee M.; Taylor, Sarah A.; Kelly, Susan; Alonso, Estella M.
ABSTRACT: Objectives: Liver biopsy can be a valuable tool to help determine the etiology of pediatric acute liver failure (PALF), but is often not performed due to safety concerns. The primary aim was to describe the incidence of major complications after liver biopsy performed in the setting of PALF. Methods: Medical records from 2006 to 2016 were reviewed. Patients age 0 to 17 years, who met criteria for PALF, and had a liver biopsy performed while their international normalized ratio (INR) was ≥1.5 were included. Results: A total of 26 cases of liver biopsy in the setting of PALF were identified. The majority (n = 22, 85%) of patients had primary liver disease. Most biopsies (n = 17, 65%) were performed by the transjugular route, with 5 (19%) performed percutaneously under ultrasound guidance and 4 (15%) during a surgical procedure. Median INR before biopsy was 2.1 (IQR = 1.73–2.9). Blood products were given before or during the procedure in 23 (88%) cases. One patient (3.8%) had a major complication of biopsy-associated bleeding requiring a blood transfusion. An additional 3 patients had a hemoglobin decrease of 2.1 to 2.9 g/dL post-biopsy that was attributed to the procedure but no interventions were necessary. Biopsy results contributed to establishing a diagnosis in 62% (n = 16) of cases, and influenced treatment decisions in 9 of those cases. Conclusions: Liver biopsy is safe in the majority of patients with PALF and associated with infrequent major complications. Clinicians should consider performing liver biopsy in this setting, especially when the transjugular approach is feasible, since findings may guide diagnosis and therapy. Abstract : Supplemental Digital Content is available in the text